Potential effects of neonicotinoid insecticides on northern bobwhites. (23rd October 2018) - Ertl, Hannah M.; Mora, Miguel A.; Boellstorff, Diane E.; Brightsmith, Donald; Carson, Katherine
ABSTRACT: Northern bobwhite ( Colinus virginianus ) populations have been declining in Texas, USA, for nearly 3 decades. Reasons for the decline are unclear; however, a variety of factors have been considered, including pesticides and other environmental contaminants. We assessed potential effects of neonicotinoid insecticides on bobwhites by analyzing liver tissues from specimens collected in 3 selected regions of Texas. Fifty‐seven bobwhites were collected from the South Texas Plains, Rolling Plains, and Gulf Coast Prairies and Marshes regions during autumn 2014 and spring 2015. Neonicotinoid compounds were detected in trace amounts in the livers of 7 quail, including samples from all 3 field sites and during both collecting periods. Signs of testicular degeneration ( n = 2) and hepatocellular vacuolation ( n = 10) were consistent with known results of neonicotinoid intoxication. Overall, we identified evidence of bobwhite exposure to neonicotinoid insecticides, which correlates with a previous study that suggests that neonicotinoid use may be contributing to quail decline in some ecoregions in Texas, particularly the High Plains, Rolling Plains, Gulf Coast Prairies and Marshes, South Texas Plains, and Edwards Plateau. © 2018 The Wildlife Society. Abstract : Neonicotinoid compounds were detected in trace amounts in the livers of northern bobwhite quail. Signs of testicular degeneration ( n = 2) and lipid‐type hepatocellular vacuolation ( n = 8) were consistent with known results of neonicotinoid intoxication. A population‐level ecological risk assessment would provide a more complete understanding of the impacts of neonicotinoid use in Texas, USA, on bobwhite population declines.